Autophagy Modulators in Coronavirus Diseases: A Double Strike in Viral Burden and Inflammation - Silva, Rafael Cardoso Maciel Costa; Ribeiro, Jhones Sousa; da Silva, Gustavo Peixoto Duarte; da Costa, Luciana Jesus; Travassos, Leonardo Holanda (Frontiers in Cellular and Infection Microbiology, 2022)
Coronaviruses are the etiologic agents of several diseases. Coronaviruses of critical medical importance are characterized by highly inflammatory pathophysiology, involving severe pulmonary impairment and infection of multiple cell types within the body. Here, we discuss the interplay between coronaviruses and autophagy regarding virus life cycle, cell resistance, and inflammation, highlighting distinct mechanisms by which autophagy restrains inflammatory responses, especially those involved in coronavirus pathogenesis. We also address different autophagy modulators available and the rationale for drug repurposing as an attractive adjunctive therapy. We focused on pharmaceuticals being tested in clinical trials with distinct mechanisms but with autophagy as a common target. These autophagy modulators act in cell resistance to virus infection and immunomodulation, providing a double-strike to prevent or treat severe disease development and death from coronaviruses diseases.